A study of acrolectal Malaysian English pronunciation / Devan Gunaseelan - Devan, Gunaseelan (2018)
Most descriptions of Malaysian English (MalE) pronunciations focus on the colloquial and learner varieties. One of the reasons for this is the assumptions that MalE refers to the localised and more colloquial variety. The other is the assumption that the standard variety of MalE is similar to Standard British English (SBE). Whilst this may be true of the written standard variety, it is unlikely Malaysian speakers sound like SBE speakers or speak with a Received Pronunciation (RP) accent. However, there is a lack of research published in the area pertaining in the spoken variety of acrolectal MalE. One of the implications of this gap is the deference to RP as a reference point. To address this gap the current study sets out to identify the features of vowels and consonants in the acrolectal variety of MalE through an analysis of the pronunciations of Malaysian newscasters. The main reason for selecting broadcast English for this research is that we would expect the acrolectal variety of English to be used in this context. Extracts from ten newscasters, from two Malaysian English news channels were selected for the research. Perceptual analysis was supplemented by acoustic analysis of the sounds where relevant. The results indicate that the pronunciation of acrolectal MalE exhibits limited similarities to the spoken colloquial variety of MalE particularly in relation to the initial th stopping, a lack of vowel contrast and the realisation of some diphthongs as monophthongs. In conclusion, the acrolectal MalE is not similar to BrE, as previously maintained, and it is also not similar to the colloquial variety or learner variety which tends to have more marked pronunciation features.